Fungus-growing insects host a convergent microbiome with functional similarities to other lignocellulose-feeding insects - Barcoto, Mariana de Oliveira [UNESP] (2017)
Fungus-growing insects (ants, termites, and beetles) independently evolved a symbiotic association with fungi that metabolize recalcitrant plant biomass, producing nutrients available to the insect host. These fungicultural systems also harbor bacterial microbiota of important physiological impacts for the host life style. Here, we explore convergence patterns of the microbiota associated with fungiculture systems. For expanding the geographic distribution of microbiomes fungiculture systems available, we sequenced and annotated metagenomes of bacterial communities from Mycocepurus goeldii (lower Attini ant) and Atta sexdens rubropilosa (higher Attini, a leaf-cutter ant), the first attine ants’ microbiomes from South America. Pseudomonas, Pantoea, Rhizobium, Enterobacter, Achromobacter, Stenotrophomonas and Serratia were the most abundant genera in the bacterial community of A. sexdens rubropilosa fungus garden. Similarly, Pseudomonas was also the most abundant genus in the bacterial community of M. goeldii fungus garden, followed by Dysgonomonas, Bacteroides, Parabacteroides, Prevotella, Comamonas and Burkholderia. For metabolic profiling, these microbiomes were included in comparisons of several levels: between lower and higher attines, among fungus-growing insects, and between fungus-growing and non-fungus-growing insects. Comparative analysis of fungus-growing insects associated microbiomes support remarkable functional and taxonomic similarities, pointing to convergence in bacterial communities. Metabolic parallels may be found among microbiomes from fungus-growing insects and other lignocellulose-feeding insects, particularly for pathways involved with the metabolism of carbohydrates, amino acids, aromatic compounds, cofactors and vitamins. However, there are substantial taxonomic differences between microbiomes from fungiculture systems and herbivorous insects’ gut, giving further evidence for the functional convergence in bacterial microbiota associated with fungus-growing insects.